Estimating the daily dry matter intake of Svalbard reindeer in late winter - Tyler, Nicholas (Rangifer, 1987)
Svalbard reindeer (Rangifer tarandus platyrhynchus) store large reserves of subcutaneous fat during summer and autumn which, it has been suggested, might be sufficient to meet a substantial part of their energy requirements during winter. An alternative suggestion, however, is that fat is not their main source of energy after all and, moreover, that the principal role of their fat reserves is for enhancing reproductive success rather than for substituting for forage (Tyler, in press). Is it realistic to suggest that these high arctic herbivores could meet the greater part of their energy requirements in winter by feeding, given that the aerial biomass of available forage in Svalbard in late winter is very low? This question was investigated by using a simple model to predict what rate of food intake Svalbard reindeer would have to achieve to maintain energy balance in late winter. The results were surprisingly low: pregnant and nonpregnant females could mett their daily energy demands by consuming 3.1 and 1.7 g dry matter per grazing minute, respectively. This supports the suggestion that Svalbard reindeer could live principally off forage in winter.